معوقات استخدام الألعاب التعليمية الإلكترونية في التعليم من وجهة نظر معلمات الطفولة المبكرة - العنزي، نهلى موسى عيد (مؤسسة تربية الطفولة المبكرة, 2022)
هدفت الدراسة إلى التعرف على معوقات الألعاب التعليمية الإلكترونية من وجهة نظر معلمات الطفولة المبكرة؛ ولتحقيق الأهداف استخدمت الدراسة المنهج الوصفي المسحي، وقد تكون مجتمع الدراسة من (1528) معلمة في مرحلة الطفولة المبكرة، أما عينة الدراسة فقد تكونت من عينة عشوائية بسيطة من المعلمات بلغ حجمها (30) معلمة. وتوصلت الدراسة إلى مجموعة من النتائج وهي: يواجهن معلمات الطفولة المبكرة معوقات إدارية ومعوقات فنية وتتعلق بالبنية التحتية تعيق استخدام الألعاب التعليمية الإلكترونية في التعليم. لا توجد فروق دالة إحصائيا في تقديرات معلمات الطفولة المبكرة للمعوقات الإدارية والفنية والمعوقات التي تتعلق بالبنية التحتية التي تواجههن أثناء استخدامهن للألعاب التعليمية الإلكترونية وفقا للخبرة في التدريس. لا توجد فروق دالة إحصائيا في تقديرات معلمات الطفولة المبكرة للمعوقات الإدارية والمعوقات التي تتعلق بالبنية التحتية التي تواجههن أثناء استخدامهن للألعاب التعليمية الإلكترونية وفقا للمؤهل العلمي. توج د فروق دالة إحصائيا في تقديرات معلمات الطفولة المبكرة للمعوقات الفنية التي تواجههن أثناء استخدامهن للألعاب التعليمية الإلكترونية وفقا للمؤهل العلمي وجاءت لصالح مؤهل البكالوريوس. وفي ضوء نتائج الدراسة أوصت الباحث بالتالي: عقد دورات تدريبية تهدف إلى توعية المدارس والإدارات التعليمية بتفعيل استخدام الألعاب التعليمية الإلكترونية في التعليم. تضمين استخدام الألعاب التعليمية الإلكترونية في العملية التعليمية، واختيار الألعاب الإلكترونية التي تناسب أعمار الأطفال. The study aimed to identify the obstacles of electronic educational games from early childhood teachers' perspective. The study used the descriptive survey approach to achieve the objectives. The study population consisted of (1528) early childhood teachers, while the study sample consisted of a simple random sample of (30) female teachers. The study reaches a set of results. They are: - early childhood teachers face administrative and technical obstacles and obstacles related to infrastructure which hinder the use of electronic educational games in education. - There are no statistically significant differences in the estimates of early childhood teachers of administrative, technical and infrastructure obstacles which they face while using electronic educational games according to teaching experience. - There are no statistically significant differences in the estimates of early childhood teachers of administrative and infrastructure obstacles that they face while using electronic educational games according to the educational qualification. - There are statistically significant differences in the estimates of early childhood teachers of the technical obstacles they face while using electronic educational games according to the educational qualification. They are in favor of the bachelor's degree. In light of the results, the researcher recommended the following: Holding training courses aims at educating schools and educational administrations to activate the use of electronic educational games in education. Including the use of electronic educational games in the educational process and choosing electronic games that suit the ages of children
Keywords: التعليم الإلكتروني -- الألعاب التعليمية الإلكترونية -- معلمات رياض الأطفال -- الطفولة المبكرة